Understanding Tax Avoidance Behavior: The Interplay of Audit Quality, Company Size, and Audit Committee in Islamic Commercial Banks in Indonesia - Chairunisa, Mariyam; Sarpingah, Siti (Jurnal Profita: Komunikasi Ilmiah Akuntansi dan Perpajakan, 2023)
Taxation plays a pivotal role in the economy as it constitutes the primary source of revenue for a nation, Indonesia included. By imposing taxes across all sectors, it undoubtedly fuels developmental endeavors. In this research, we investigate how audit quality and company size influence tax avoidance, with the moderation of audit committees, within Islamic commercial banks operating in Indonesia between 2016 and 2021. One of the highest state revenues is supported by the taxation sector. Tax revenues are used to finance state spending as well as for state development. Efforts to optimize tax sector revenue are not without obstacles. Companies tend to take action to minimize or minimize tax costs by exploiting weaknesses in tax regulations, one of the actions taken is tax avoidance.. The research method used is the saturated sample method which uses secondary data in the form of annual reports of fourteen Islamic commercial banks in Indonesia that provide Annual Reports. The data obtained were processed by multiple linear regression analysis using SPSS statistical tools. The results of the study state that audit quality has a significant and negative effect on tax avoidance. However, company size has no effect on tax avoidance. The audit committee can strengthen the relationship between audit quality and tax avoidance. On the other hand, the audit committee is not able to strengthen the effect of company size on tax avoidance. This research is expected to be a reference for further research.